2014
DOI: 10.1186/s12939-014-0118-y
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic inequalities are still a barrier to full child vaccine coverage in the Brazilian Amazon: a cross-sectional study in Assis Brasil, Acre, Brazil

Abstract: IntroductionVaccines are very important to reduce morbidity and mortality by preventable infectious diseases, especially during childhood. Optimal coverage is not always achieved, for several reasons. Here we assessed vaccine coverage for the first 12 months of age in children between 12 and 59 months old, residing in the urban area of a small Amazonian city, and factors associated with incomplete vaccination.MethodsA census was performed in the urban area of Assis Brasil, in the Brazilian Amazon, in January 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 34 publications
3
40
0
7
Order By: Relevance
“…We identified that good level of knowledge was associated with positive behavior of immunization service utilization, which is consistent with studies conducted in Nigeria and Ethiopia [ 11 , 12 ]. Approval and intention were significantly associated with immunization practice and this finding is consistent with some earlier studies conducted in Ethiopia, Brazil and Nigeria [ 11 , 13 , 14 ].…”
Section: Discussionsupporting
confidence: 89%
“…We identified that good level of knowledge was associated with positive behavior of immunization service utilization, which is consistent with studies conducted in Nigeria and Ethiopia [ 11 , 12 ]. Approval and intention were significantly associated with immunization practice and this finding is consistent with some earlier studies conducted in Ethiopia, Brazil and Nigeria [ 11 , 13 , 14 ].…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, low socioeconomic status has been found as one of the main factors associated with incomplete vaccination in Brazil [10,12,27] and around the globe [28]. It is worth mentioning that, in our analyses, higher coverage of incomplete immunization was also found among the poorest when compared with the three middle quintiles of family income (Additional file 3).…”
Section: Discussionmentioning
confidence: 51%
“…Discussão O presente estudo evidenciou alta cobertura das vacinas de múltiplas doses e do esquema vacinal básico completo nos pacientes de 0 a 2 anos de idade cadastrados no CMS estudado. Quanto às características relacionadas ao atraso, outros estudos apontam que as crianças mais prováveis de completarem o esquema vacinal são aquelas de menor idade, 13,14 o que está em consonância com este trabalho. A não vacinação dos filhos de idade superior pode talvez ser justificada pela ARTIGO condição de concorrência entre irmãos mais velhos em busca do cuidado parental limitado ou pela insuficiência quanto a recursos para abastecer o número de crianças no domicílio.…”
Section: Resultadounclassified